DAMPAK KEBIJAKAN BIAYA PENDIDIKAN TERHADAP AKSES DAN PARTISIPASI SISWA MADRASAH IBTIDAIYAH MUHAMMADIYAH SIDOKERTO, PLUPUH, SRAGEN - Isnaini Isnaini; Harsono MS (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research examines how education-cost policies shape access and participation in a community-based Islamic primary school, focusing on Madrasah Ibtidaiyah (MI) Muhammadiyah Sidokerto, Plupuh, Sragen, which serves 352 students with 20 teachers. The research aims to explain why “school costs” remain a meaningful determinant even when the government expands operational support and establishes education financing standards. A descriptive case-study design is employed by combining policy review and school-level financing mapping to identify cost components borne by schools and households. The findings highlight three patterns. Operational support reduces barriers related to routine school fees, yet indirect costs—such as uniforms, transportation, learning materials, and informal contributions—remain decisive for families. Participation is more than enrolment: continuity of attendance, learning engagement, and involvement in extracurricular activities are sensitive to household cash flow and the timing of support received. School governance also plays a decisive role in translating policy into real relief through transparent budgeting, fair targeting of subsidies, and flexible payment arrangements.